Enhancing Innovation Through Knowledge Sharing and Quality Leader–Member Relationships - Denpharanto Agung Krisprimandoyo; Mohamad Yusak Anshori; Jamilah Ahmad; Siska Armawati Sufa; Garry Brumadyadisty (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
The impact of leader member exchange on enhancing innovation capacity, especially for employees with more than 15 years of experience in situations where knowledge exchange is limited, is an important area of research. This study highlights the positive influence of strong personal relationships between managers and senior employees on innovation, even in the absence of in-depth knowledge exchange. This emphasizes the important role of LMX in encouraging experienced employees to share knowledge and expertise and utilize their accumulated knowledge. This study uses a quantitative method with a Structural Equation Modeling approach to analyze the structural relationships between latent variables based on questionnaire data from 194 employees of PT. Ciputra Nusantara. The findings highlight the importance of strong interpersonal relationships and leadership influence in overcoming low barriers to knowledge sharing, thereby enhancing senior employees' innovation capabilities. Practical implications include the development of leadership training that fosters strong personal relationships and helps employees gain experience in contributing to innovation efforts, even in environments where knowledge sharing is a common practice. This study provides new insights into strategic leadership and human resource management, highlighting the important role of leader member exchange in overcoming knowledge sharing challenges in organizations.